Pornografl-Pornoaksi Dalam Perundang-Undangan dan Perjuangan Membebaskan Perempuan - Zulfa, Kholid (Musawa Jurnal Studi Gender dan Islam, 2006)
Women still have to make hard effort to strive for liberating themselves. As most of them persistently fight for gender equality to gain their equal rights before men, and when men's sympathy hugely grows to take women as their equal contenders, many other women at the same time enjay being involved in pornography and porno-action. They harm people by committing sex exploitation in various actions. The question then comes up, how the acts govern the pornography and porno action and what impact it will make for women's struggle. This article describes the constitutions regulating porno. graphy and porno-action and elaborates the impact of pornography-porno action towards the entire women's liberation struggle. The term of porno. graphy-porno action, scope, and the object used in criminal laws vary in many countries. They use it both explicitly or implicitly in which the judge's reasoning plays a large role within it. Terminologically, the word of porno. graphy-pomo-action is not found in Indonesian Criminal Law. Nevertheless, it is substantially stated by: Crime against Norms. we can read that in chapters 281, 282, 283, 532 and533 Â of Criminal Law.